PENGARUH KECANDUAN GAME ONLINE TERHADAP KESEHATAN MENTAL SISWA SMAI NFBS LEMBANG - VINA LUSIANA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
Online games are one of the technological products that provide entertainment benefits, namely online games, namely games that are played by more than one player in groups via the internet network. In this case, teenagers will always want to play games, and eventually become addicted to games. Teenagers who like to play games turn into teenagers who behave compulsively, aggressively, ignorant of activities and the surrounding environment. One of the mental disorders that can occur in online game addicts is depression. Depression can be a risk factor for someone to become an online game addict, but it can also be a result of online game addiction. There are many impacts caused by online game addiction, ranging from social, psychological, and health impacts. Therefore, researchers intend to conduct research on online game addiction in SMAI NFBS Lembang students. The title of this study is